2022
DOI: 10.3390/en15249653
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Ashes from Biomass Combustion

Abstract: Biomass is one of the most important sources of renewable energy in the energy industry. It is assumed that by 2050 the global energy deposit could be covered in 33–50% of biomass combustion. As with conventional fuels, the combustion of biomass produces combustion by-products, such as fly ash. Therefore, along with the growing interest in the use of biomass as a source of energy, the production of ash as a combustion by-product increases every year. It is estimated that approximately 476 million tons of ashes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…( 2011 ). Ash represents the inorganic residues in plant biomasses, thus showing the level of mineral residues such as Ca, Mg, K, Na, Fe, Zn, P, and Cl (Odzijewicz et al., 2022 ; Tiroesele et al., 2013 ). High mineral content in foods promotes growth and development by catalyzing metabolic processes in the human body.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2011 ). Ash represents the inorganic residues in plant biomasses, thus showing the level of mineral residues such as Ca, Mg, K, Na, Fe, Zn, P, and Cl (Odzijewicz et al., 2022 ; Tiroesele et al., 2013 ). High mineral content in foods promotes growth and development by catalyzing metabolic processes in the human body.…”
Section: Resultsmentioning
confidence: 99%
“…The mean ash content of oven-dried Kenkeste and Sharma was 8.01 g/100 g and 7.31 g/100 g, respectively, which is consistent with the levels reported by . Ash represents the inorganic residues in plant biomasses, thus showing the level of mineral residues such as Ca, Mg, K, Na, Fe, Zn, P, and Cl (Odzijewicz et al, 2022;Tiroesele et al, 2013). High mineral content in foods promotes growth and development by catalyzing metabolic processes in the human body.…”
Section: Total Ash Contentmentioning
confidence: 99%
“…The studies (Bo et al, 2022;Odzijewicz et al, 2023) identified that symbiotic nitrogen of perennial legumes both in legume-cereal mixtures and in single-species crops improves the chemical composition of feed. In particular, it helps to increase the content of crude protein, protein, macroelements of calcium and magnesium in the dry mass, improve the digestibility of feed, the nutritional content of feed units and energy intensity in the content of metabolic energy, and reduce the amount of nitrogen-free extractives, crude fibre, and potassium.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the intensification of biomass development [3], new fuels need to be considered. As shown by [4], new fuels comparable to standard fuels, such as RDF or challenging biomasses, could be considered, but they present some challenges (corrosion with ashes [5]), particularly for conventional grate grid furnaces. Some studies have evaluated the ability to mix the product during combustion to push the technological limits of the grate [6].…”
Section: Introductionmentioning
confidence: 99%